Transformation of Scientific Paradigms: Philosophical and Practical Studies of Transdisciplinary Approaches - Putera, Faga Pandunata; Fitrohah, Irgy Mahbub (Jurnal Indonesia Sosial Sains, 2026)
Scientific integration is an important issue in the development of contemporary science, especially within the environment of Islamic religious higher education. The integration practices that have developed so far are often still partial and symbolic; therefore, they are not able to adequately address complex and multidimensional social problems. The transdisciplinary approach emerges as an epistemological framework that seeks to transcend disciplinary boundaries by integrating diverse scientific perspectives, human values, and social contexts in a holistic manner. This study aims to examine transdisciplinary approaches within the framework of scientific integration, including their concepts, methodologies, objectives and benefits, forms of implementation, and implementation challenges. This study employs a qualitative approach using a literature review method. Data were obtained through the identification and analysis of books, scientific journal articles, and relevant academic literature, and were subsequently analyzed using descriptive-analytical techniques. The results of the study indicate that the transdisciplinary approach plays a strategic role in building holistic and contextual scientific integration; however, its implementation still faces several challenges, including differences in scientific paradigms, difficulties in methodological integration, and barriers to cross-disciplinary communication.